Training the next generation of South African cardiologists – Are we on the right track? - Doubell, Anton (SA Heart Journal, 2017)
The training of cardiologists in South Africa has changed markedly over the last 20 years. Training centres across the country have accepted the challenge and continue to produce cardiologists of a high standard. Testament to this fact are the many South African trained cardiologists who have made their mark as leaders in the field of cardiology in the USA, UK and Europe as well as the number of applicants from other countries seeking to be trained at South African institutions. However, we should remember the advice of our colleague from endocrinology and we should embrace the belief that everything can improve.